The Spindlers - Oliver, Lauren, 1982- (Harper, 2012)
Accompanied by an eccentric, human-sized rat, Liza embarks on a perilous quest through an underground realm to save her brother, Patrick, whose soul has been stolen by the evilest of creatures--the spider-like spindlers.